Psycholinguistic Mechanisms of Classifier Processing in Sign Language - Krebs, Julia; Malaia, Evie; Wilbur, Ronnie B; Roehm, Dietmar (Journal of experimental psychology. Learning, memory, and cognition, 2021)
Nonsigners viewing sign language are sometimes able to guess the meaning of signs by relying on the overt connection between form and meaning, or iconicity (cf. Ortega, Özyürek, & Peeters, 2020; Strickland et al., 2015). One word class in sign languages that appears to be highly iconic is classifiers: verb-like signs that can refer to location change or handling. Classifier use and meaning are governed by linguistic rules, yet in comparison with lexical verb signs, classifiers are highly variable in their morpho-phonology (variety of potential handshapes and motion direction within the sign). These open-class linguistic items in sign languages prompt a question about the mechanisms of their processing: Are they part of a gestural-semiotic system (processed like the gestures of nonsigners), or are they processed as linguistic verbs? To examine the psychological mechanisms of classifier comprehension, we recorded the electroencephalogram (EEG) activity of signers who watched videos of signed sentences with classifiers. We manipulated the sentence word order of the stimuli (subject-object-verb [SOV] vs. object-subject-verb [OSV]), contrasting the two conditions, which, according to different processing hypotheses, should incur increased processing costs for OSV orders. As previously reported for lexical signs, we observed an N400 effect for OSV compared with SOV, reflecting increased cognitive load for linguistic processing. These findings support the hypothesis that classifiers are a linguistic part of speech in sign language, extending the current understanding of processing mechanisms at the interface of linguistic form and meaning.